Measurement of the polarization amplitudes and triple product asymmetries in the B0s→ [phi][phi] decay* - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Gersabeck, Evelina; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; Holubyev, Kostya; Jäger, Andreas; et al. (Physics letters, 2012)
Heavy quark production in 7 TeV centre-of-mass energy pp collisions at the LHC is not necessarily flavour symmetric. The production asymmetry, AP, between Ds+ and Ds− mesons is studied using the ϕπ± decay mode in a data sample of 1.0 fb−1 collected with the LHCb detector. The difference between π+ and π− detection efficiencies is determined using the ratios of fully reconstructed to partially reconstructed D⁎± decays. The overall production asymmetry in the Ds± rapidity region 2.0 to 4.5 with transverse momentum larger than 2 GeV is measured to be AP=(−0.33±0.22±0.10)%. This result can constrain models of heavy flavour production.
Available online 8 June 2012
Im Titel sind "0" und "s" untereinander geschrieben: "0" hochgestellt, "s" tiefgestellt
Im Titel ist "phi" als griechischer Buchstabe dargestellt
Gesehen am 26.06.2018
LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, J. Blouw, F. Dordei, F. Eisele, C. Fäber, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, K. Holubyev, A. Jaeger, K. Kreplin, G. Krocker, P. Krokovny, C. Langenbruch, C. Linn, J. Marks, P. Seyfert, S. Stahl, J. v. Tilburg, U. Uwer, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]